Formação continuada do professor que ensina matemática nas séries iniciais do ensino fundamental: um estudo a partir da produção acadêmico-científica brasileira (2003 2007) - Marim, Vlademir (2011)
The objective of this thesis has been to show and analyze the principal contributions of Brazilian scientific-academic productions, to comprehend the reality of continued formation of teachers in the first grades of Elementary School, specifically in the area of Mathematics , through defended and published dissertations and thesis during the period of 2003 to 2007, at Institutions of Higher Education with a grading of 5,6 or 7, with the aim of enhancing programs of continued formation that are being implanted in the different municipalities. The methodology developed corresponds to what is called The State of Art, which in this case has as its objective a systemization of information production concerning the continued formation of teachers in the beginning grades of Basic Education in the teaching of Mathematics. A data analysis was realized based on three guiding axis: theoretic references aiming at continued formation; suggested programs and pedagogical practices for continued formation; programs and concrete proposals for enhancement in continued formation. With basis on theoretic references, the analyzed results suggest that the teaching of Mathematics occurs effectively starting from the changes in paradigms and breaking away from beliefs, through contextualization and application of innovative methods. For this, it is necessary to increase the number of continued formation programs, that the school leaders also know the development and practice theory of the process of formation so that they are able to support the work of the teachers in their teaching practice and that this formation contemplates the personal needs of the teachers and of the group the work in a determined region, as well as the needs of the regions. It is necessary to rethink the actions of the faculty, the contents and methodological strategies, searching to better the initial formation of the teacher, without forgetting the needs that contemplate a continued formation, because the world is in constant change, it is imperative that the teacher follow this evolution